2014
DOI: 10.4103/0970-4388.140943
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of canal transportation and centering ability of K 3 (0.02%) and K 3 (0.04%) with hand K files in primary teeth using spiral computed tomography

Abstract: K 3 (0.02% taper) shaped root canals without significant shaping errors when compared to K 3 (0.04% taper) and stainless steel hand K files in primary teeth.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 1 publication
0
9
0
Order By: Relevance
“…The two different degrees of tapered K 3 rotary files (.02 and .04) have been used to analyse the utmost K 3 files for primary root canal preparation. Previous study done by Selvakumar et al, using a similar concept and methodology assessed the canal transportation and canal centring ability [10]. The purpose of the present study was to compare the amount of dentine removed, the risk of perforation and instrumentation time of rotary (K 3 file) and manual (K-file) instruments in preparing primary molars.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The two different degrees of tapered K 3 rotary files (.02 and .04) have been used to analyse the utmost K 3 files for primary root canal preparation. Previous study done by Selvakumar et al, using a similar concept and methodology assessed the canal transportation and canal centring ability [10]. The purpose of the present study was to compare the amount of dentine removed, the risk of perforation and instrumentation time of rotary (K 3 file) and manual (K-file) instruments in preparing primary molars.…”
Section: Methodsmentioning
confidence: 99%
“…The third slice from the apical end of the tooth was used to assess the apical section [Table /Fig1a]. For the purpose of standardization, four reference points were taken on the outer walls of the distal root as buccal (A), lingual (B), mesial (C) and distal (D) points [10].…”
Section: Specimen Scanningmentioning
confidence: 99%
“…On the other hand, rotary instrumentation dramatically reduces the working time, which is a very interesting aspect to consider for pediatric patients (1,(3)(4)(5)(6)(7)(8)(9)(10).…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, two recent studies (9,10) showed the use of computed tomography (CT) in the assessment of root canal preparation of primary teeth. Is noteworthy that although there are no studies that assess the biomechanical preparation in primary teeth using micro-computed tomography (micro-CT), this methodology has been commonly used for this purpose in permanent teeth, as it allows a three-dimensional noninvasive assessment of the RCS and root canal preparation (12,(14)(15)(16).…”
Section: Introductionmentioning
confidence: 99%
“…Smaller the ratio, the better the instrument will remain centered in the canal. 8 In this study canal transportation was determined by the formula developed by Gambill et al : (X 1 -X 2 ) -(Y 1 -Y 2 ). 8,9 Where, X 1 is the shortest distance from the outside of the canal to the periphery of the uninstrumented canal.…”
Section: Discussionmentioning
confidence: 99%